Evaluating subscore uses across multiple levels: A case of reading and listening subscores for young EFL learners. (April 2020) - Choi, Ikkyu; Papageorgiou, Spiros
Stakeholders of language tests are often interested in subscores. However, reporting a subscore is not always justified; a subscore should provide reliable and distinct information to be worth reporting. When a subscore is used for decisions across multiple levels (e.g., individual test takers and schools), it needs to be justified for its reliability and distinctiveness at every relevant level. In this study, we examined whether reporting seven Reading and Listening subscores of the TOEFL Primary ® test, a standardized English proficiency test for young English as a foreign language learners, could be justified for reporting at individual and school levels. We analyzed data collected in pilot administrations, in which 4776 students from 51 schools participated. We employed the classical test theory (CTT) based approaches of Haberman (2008) and Haberman, Sinharay, and Puhan (2009) for the individual and school-level investigations, respectively. We also supplemented the CTT-based approaches with a factor analytic approach for the individual level analysis and a multilevel modeling approach for the school-level analysis. The results differed across the two levels: we found little support for reporting the subscores at the individual level, but strong evidence supporting the added-value of the school-level subscores when the sample size for each school exceeds 50.